2020
DOI: 10.4269/ajtmh.19-0943
|View full text |Cite
|
Sign up to set email alerts
|

Cost-Effectiveness Analysis of Sex-Stratified Plasmodium vivax Treatment Strategies Using Available G6PD Diagnostics to Accelerate Access to Radical Cure

Abstract: Tafenoquine has been licensed for the single-dose radical cure of Plasmodium vivax in adults; however, it is only recommended in patients with > 70% of normal glucose-6-phosphate dehydrogenase (G6PD) activity. Because this may hinder widespread use, we investigated sex-based treatment strategies in which all adult patients are tested with a qualitative G6PD rapid diagnostic test (RDT). Glucose-6-phosphate dehydrogenase normal males are prescribed tafenoquine in all three strategies, whereas G6PD normal females… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
10
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
8
1

Relationship

1
8

Authors

Journals

citations
Cited by 11 publications
(10 citation statements)
references
References 35 publications
0
10
0
Order By: Relevance
“…Even those who will not be prescribed tafenoquine will benefit from radical cure in Brazil, as patients with G6PD activity of 30–70% will receive 7-day primaquine and those with <30% activity will receive weekly primaquine. Sex-guided treatment strategies may potentially ensure widespread use of tafenoquine for radical cure in low resource settings [ 37 ]. Future research should examine the ICER of tafenoquine.…”
Section: Discussionmentioning
confidence: 99%
“…Even those who will not be prescribed tafenoquine will benefit from radical cure in Brazil, as patients with G6PD activity of 30–70% will receive 7-day primaquine and those with <30% activity will receive weekly primaquine. Sex-guided treatment strategies may potentially ensure widespread use of tafenoquine for radical cure in low resource settings [ 37 ]. Future research should examine the ICER of tafenoquine.…”
Section: Discussionmentioning
confidence: 99%
“…Thus, for rolling out TQ in endemic areas, more stringent screening of G6PD activity with quantitative tests is needed [111,140]. A recent cost-effectiveness analysis suggests that TQ may be deployed in endemic areas outside sub-Saharan Africa using a gender-specific strategy where G6PD-normal females can be prescribed a low-dose PQ for 14 days [141]. This approach again centers on the availability of a qualitative G6PD test.…”
Section: G6pd Deficiency and Point-of-care Testingmentioning
confidence: 99%
“…In a study conducted in Vietnam, Indonesia, Afghanistan, and Ethiopia on the sex-based treatment for Pv radical cure, G6PD qualitative tests were used with the referral services for G6PD quantitative tests. Female patients with normal G6PD results were referred to a different facility for G6PD quantitative tests and further Pv radical cure treatment with Tafenoquine [ 21 ]. The study reported that referral of female patients for G6PD quantitative tests was less cost-effective than the non-referral option where PMQ 7 days regimen was provided after the normal result from G6PD qualitative tests.…”
Section: Introductionmentioning
confidence: 99%
“…The study reported that referral of female patients for G6PD quantitative tests was less cost-effective than the non-referral option where PMQ 7 days regimen was provided after the normal result from G6PD qualitative tests. However, only qualitative G6PD test was studied among males [ 21 ].…”
Section: Introductionmentioning
confidence: 99%